NILAI MORAL DALAM NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SIRAZY SEBAGAI ALTERNATIF BAHAN AJAR SASTRA DI SMA KELAS XII: SEBUAH KAJIAN PRAGMATIK* (Moral Values of the Habiburrahman El Shirazy’s Novel: Bidadari Bermata Bening as an Alternative Literature Teaching Material in Grade XII Senior High School) - Ningsih, Dwining Dyah Hadi; Sri Sudaryanti, Rina Ratih (Balai Bahasa Jawa Tengah, 2019)
This study discusses moral values in Habiburrahman El Shirazy?s novel: Bidadari Bermata Bening. The aim of this research is to describe the principle of good attitude, the principle of justice, the principle of respecting oneself in the Bidadari Bermata Bening using a pragmatic approach, and its relation to literary teaching materials. Data collection methods used are observation, reading techniques, and literature review. The results of this study are as follows. (1) Moral values based on the principle of good attitude in the novel are the values of being responsible, happy to help, and loyal in everyday life. (2) Moral value based on the principle of fairness in this novel is awareness to give the rights of others. (3) Moral valuess based on the principle of respecting oneself are the value of protecting themselves and maintaining their honor. (4) This novel has fulfilled the criteria of teaching material so that it can be used by teachers as an alternative in literary teaching materials in class XII senior high school. Keywords: moral values, novel, teaching material